Fermion mass formulation in the Modified Left-Right Symmetry Model - Nurul Embun Isnawati; Istikomah Istikomah; Muhammad Ardhi Khalif (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2022)
The Modified Left Right Symmetry Model is an extension of the Standard Model. This model introduces left-handed neutrinos to the right sector and a doublet scalar field to the left sector. This model cannot yet explain the mass generation of fermions and neutrinos. This study is theoretical research using the literature review method. Generating the masses of fermions (quark up-down) and electrons through spontaneous symmetry breaking in Yukawa's Lagrangian term produces a particle mass in the left sector, the same as the calculations in the Standard Model. The masses of fermions (up-down quarks) and electrons for the right sector produced in this study are much more massive than those of fermions (up-down quarks) and the left sector. The neutrino masses produced in this study are by following the Seesaw Mechanism. That is, if one neutrino mass is massive, then the other neutrino masses will be light.©2022 JNSMR UIN Walisongo. All rights reserved.